(3hLgI fXQ eYGUQIs - (3MSjf Pfhf Ydj(B, (3GdHjGJjs ((3YeGf(B:s (3OGQ hGFd ddfTQ(B,s, 2005)
(3pjDcO GdHGMKhf GdeJNUUhf aj Mbd EOGQI GdeSJTajGJ Ydi VQhQI eQGYGI YOO ef GdeYGjjQ GdJUejejI YfO GdTQhY HEfTGA eSJTai LOjO Ch EVGaI CLfMI hCbSGe LOjOI Edi GdeSJTajGJ GdMGdjI ,hCf jJe GdJfSjb Hjf GdgjFI GdafjI hGdLgGJ GdEOGQjI dJQLeI gPg GdeYGjjQ EdihGbY aYdj Ydi GdfMh GdPj jSgd aj LYd GdeSJTai CaVd COGA YfO EfLGR CfTWJg (B. (3EP CXgQJ GdOQGSGJ hGdHMhK Cf GdeSJTajGJ GdJj CgedJ ajgG GdeYGjjQ GdJUejejI hGLgJ UYhHGJ cKjQI YfO GfLGR CfTWJgG h jMJhj GdcJGH Ydi (B: (3ebOeI , GdeYGjjQ GdJUejejI ddeSJTajGJ , GdeYGjjQ GdEOGQjI ddeSJTajGJ ,eYGjjQ GdJbGfI GdUMjI aj GdeSJTajGJ ,eYGjjQ Jbhje GdCOGA aj GdeSJTajGJ (B.s
(3HjHdjhZQGajG U(B.121s
Keywords: (3GOGQI GdGYeGds; (3GdeSJTajGJ(B--(3GOGQIs